Interfaith Marriage Among Muslims in Singapore - Mat Hussin, Mohd Norhusairi; Binte Salihudin, Nur Haleemah; Samudin, Siti Aisyah; Risma Nur Arifah; Abdul Aziz, Norazlina; Malee, Zunairah (al-'adalah, 2025)
A new phenomenon happening in Singapore among Muslims is currently on interfaith marriage. This phenomenon has become a trend among Muslims as there is a written law in Singapore, expressly the Women's Charter, that allows marriage between Muslims and non-Muslims, which is not in line with Islamic law. Similarly, no provision in the Administration of Muslim Law Act 1966 (AMLA) specifically prohibits Muslims in Singapore from registering their marriage under Civil law with a non- Muslim spouse. This article is written to look into the factors contributing to the increase in this type of marriage, and highlight the role of the Muslim law in Singapore in relation to such marriages. The research adopts a qualitative method integrating the library and field research. The methods used are descriptive and thematic interview analysis. As a result, the writers conclude that the leading cause of the increase in interfaith marriage is the absence of Muslim law prohibiting interfaith marriage and the minimal adverse impact of such marriage. Realistically, there are contextual challenges to establish and execute a new Syariah law that prohibits the interfaith marriage among Muslims in Singapore. Therefore, this study discusses the factors contributing to the increase in Civil marriage among Muslims in Singapore and the reasons behind the absence of Muslim law prohibiting the marriage. Keywords: Singapore Syariah Law, Singapore Muslim Law, Interfaith Marriage, Interreligious Marriage.